Exploring the current state of the Bangladesh textile sector: Swot analysis from a practitioner’s viewpoint - Md. Tahzibul Haque; M. K. Wan Ibrahim; Ismail Bin Maakip; Md. Abul Kalam Azad; Ahsan Habib; Khalilullah Muhammad Bayezid; Sumaiya Siddika; Naimul Islam Bhuiyan (TWIST Journal, 2024)
The textile sector in Bangladesh is at a mature stage, accounting for more than 75% of all export earnings and ranking as the world's second-highest garment exporter behind China. In order to stay competitive in the global market despite scarce resources and other issues, this industry engages in some unethical behavior that could eventually jeopardize its long-term viability. Using a SWOT analysis, this research study explores the current state of the Bangladeshi textile industry (Strengths, Weaknesses, Opportunities, Threats) analysis. The study utilized interviews as its major data gathering method with the primary goal of gaining insights into the industry's present conditions and future expansion opportunities. Every respondent was chosen from Bangladesh with consideration for the study's goal. To achieve a thorough grasp of the textile business and gather various opinions, the research conducted in-depth interviews with management practitioners in the field. Through in-depth thematic data analysis and interpretation, the research identified the intrinsic characteristics that sustain the Bangladeshi textile industry's standing in the global market. Furthermore, the research revealed significant shortcomings that necessitate focused actions to improve sustainability and competitiveness. Furthermore, the study revealed prospective avenues for additional development and broadening within a dynamic worldwide economic environment. Ultimately, the examination exposed impending dangers that might impede the industry's advancement in the future.